2015
DOI: 10.1097/mej.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Elevated lactate level and shock index in nontraumatic hypotensive patients presenting to the emergency department

Abstract: The combination of both parameters is effective in predicting these outcome measures with higher sensitivities and NPVs. Further studies on the subject are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
0
13
2
4
Order By: Relevance
“…Lactate was found to be correlated with SI greater than 0.9 (P = 0.037 8). In the various citations we reviewed, we found no relationship between these two variables [17][18][19] .…”
Section: Discussionmentioning
confidence: 77%
“…Lactate was found to be correlated with SI greater than 0.9 (P = 0.037 8). In the various citations we reviewed, we found no relationship between these two variables [17][18][19] .…”
Section: Discussionmentioning
confidence: 77%
“…SI, a ratio that relates HR to SBP as HR/SBP, has been proposed as a simple method to assess shock severity and response to therapy in critically ill people. In a healthy adult, the SI ranges from 0.5 to 0.7, and a SI greater than 0.9 is considered high . Early work demonstrated that SI was inversely related to left ventricular stroke work in acute circulatory failure .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, SI has been proposed as a measure of hemodynamic stability as well as a marker of early hypovolemia . The value of SI in the prehospital and hospital settings in predicting both need for hospital admission and patient outcome has also been well established …”
Section: Introductionmentioning
confidence: 99%
“…In support of the rational suggestion to rely on multiple parameters for early prediction of outcome of shocked ICU patients, Cevik et al [47] found that in patients who had elevated BLL and SI, the use of mechanical ventilation and vasoactive drug was significantly higher with higher hospitalization rate and in-hospital mortality (54.1%) than in patients who had elevation of either parameter alone and concluded that combination of both parameters is effective in predicting these outcome measures with higher sensitivities and NPV. Shackelford et al [48] reported that automated analysis of triage vital signs, 15 min of pulse oximetry signals, and laboratory values including BLL predicted use of blood transfusion during trauma resuscitation more accurately than triage vital signs or pulse oximetry analysis alone.…”
Section: Discussionmentioning
confidence: 99%